2021
DOI: 10.3390/ijerph19010275
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Device-Assisted Clampless Off-Pump Coronary Artery Bypass Grafting Compared with Conventional On-Pump Technique

Abstract: Study objective: To evaluate the long-term outcomes of clampless off-pump coronary artery bypass grafting (C-OPCAB) compared with conventional on-pump double clamping coronary artery bypass grafting (C-CABG). Methods: From October 2006 to December 2011, 366 patients underwent isolated coronary artery bypass grafting. After propensity score matching of preoperative variables, 143 pairs were selected who received C-OPCAB with the use of device-assisted PAS-Port proximal venous graft anastomoses or C-CABG, perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For example, a study by Youn et al found no signifcant diference in cardiac mortality between the two procedures during a long-term follow-up in patients with reduced EF (≤35%) [30]. Similarly, a recent study by Bassano et al reported similar results, highlighting the equivalent 14-year cardiac mortality outcomes between OPCAB and ONCAB surgeries [33]. Other studies have reported similar fndings between the two groups [30,[34][35][36][37].…”
Section: Survival Probabilitymentioning
confidence: 82%
“…For example, a study by Youn et al found no signifcant diference in cardiac mortality between the two procedures during a long-term follow-up in patients with reduced EF (≤35%) [30]. Similarly, a recent study by Bassano et al reported similar results, highlighting the equivalent 14-year cardiac mortality outcomes between OPCAB and ONCAB surgeries [33]. Other studies have reported similar fndings between the two groups [30,[34][35][36][37].…”
Section: Survival Probabilitymentioning
confidence: 82%
“…We read with great interest the article by Seco and colleagues [1] based on their experience with the anaortic off-pump coronary artery bypass grafting (CABG), addressing the main advantages based on avoiding manipulation of the ascending aorta and achieving complete revascularization using multiple arterial grafts. Avoiding manipulation of the aorta has the rationale of reducing the risk of neurological complications, especially in high-risk patients affected preoperatively by previous ischemic stroke and or severe carotid artery atherosclerotic disease.…”
mentioning
confidence: 99%